PERSEPSI PETANI PADI TERHADAP ASURANSI USAHATANI PADI DI KECAMATAN RANCAEKEK KABUPATEN BANDUNG - Rizqina Qonita Aulia; Eliana Wulandari (Universitas Galuh, 2022)
Rice farming insurance program is a government program that provides income and welfare protection to farmers in the face of production risk. Drought, flooding, and attacks by plant-disturbing organisms made rice farming in Rancaekek Subdistrict, Bandung District, a threat to crop failure. The involvement of rice farming insurance program can be an effective program to protect and prosper rice farmers when there is crop failure, especially during climate-related disasters and attacks by plant destruction organisms. This study aims to analyze 1) how rice farmers in Rancaekek Subdistrict, Bandung District, express their opinions about the rice farming insurance program, 2) whether there are any differences of the perceptions between farmer groups who participated in the rice farming insurance program and those who did not. The research method utilized a survey, and the number of respondents was as many as 50 farmers using proportionate stratified random sampling. Descriptive statistical analysis and the Mann Whitneey test were used in this study. The findings show that 1) rice farmers who participated in the rice farming insurance program give a good assessment that the program is considered important and can overcome rice farming problems. This is supported by the results that farmers understand the program, the objectives and benefits of the program, and socialization activities have met the needs of farmers, the administrative process is assisted thus easier at the registration stage, file collection, and when obtaining compensation claims disbursement. Regarding the amount of insurance premiums, it is felt to be light and affordable by farmers and the cost of compensation is considered sufficient to cover the initial capital. Meanwhile, rice farmers who did not participate in the insurance program had a mixed perception, in which some farmers did not believe the benefit of the program. Some farmers were unaware of the insurance program, and as a result, they lacked a thorough understanding of the program's goals, objectives, and benefits. 2) According to the Mann Whitneey test results, there were significant differences in the perceptions between farmers who participated in the insurance program and those who did not.